2014
DOI: 10.1159/000356221
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Salvage Therapy and Its Effect on Operative Outcomes in Patients with Ulcerative Colitis

Abstract: Aims: To evaluate the efficacy and safety of salvage therapy, and to identify risk factors of operative complications among hospitalized ulcerative colitis (UC) patients. Patients and Methods: We evaluated 88 UC patients hospitalized at our center between April 2010 and November 2012. We compared characteristics of corticosteroid-refractory patients treated with calcineurin inhibitor and those with infliximab as second-line therapy. Furthermore, we compared the characteristics of operative and nonoperative pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Its incidence is increasing more rapidly in Asia than in Europe [1]. However, ­complete healing and treatment methodology for ulcerative colitis have not been established thus far [2, 3]. Disease conditions in many patients are worsening in the chronic natural course [4].…”
Section: Introductionmentioning
confidence: 99%
“…Its incidence is increasing more rapidly in Asia than in Europe [1]. However, ­complete healing and treatment methodology for ulcerative colitis have not been established thus far [2, 3]. Disease conditions in many patients are worsening in the chronic natural course [4].…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al reported that the frequency of postoperative complications did not increase in patients who underwent colectomy after receiving multiple immunosuppressive agents compared to that in patients who underwent colectomy after receiving only 1 immunosuppressive agent. 40 The benefits and risks should be carefully considered when switching between a calcineurin inhibitor and anti-TNF-α antibody therapy.…”
Section: Switching Between Tacrolimus and Anti-tnf-alpha Antibody Thementioning
confidence: 99%
“…It is known to be an effective treatment option for refractory ulcerative colitis (UC). A recent study showed that tacrolimus was effective even in the treatment for the infliximab-resistant UC as a salvage therapy [1]. In the tacrolimus treatment for UC, dose adjustment is necessary because the required doses to keep appropriate drug concentrations are significantly different among individuals.…”
Section: Introductionmentioning
confidence: 99%